Integration of Fmea in the Application of Quality Control Circle (QCC) for Quality Improvement of Production Process in Pipe Bender Machines - Ajiz, Aris Abdul; Rozak, Fatkhu; Syamsudin, Napih; Heryanto, Reifal Deri; Prastyo, Yudi (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This research aims to improve the quality of the production process on the Pipe Bender machine at PT XYZ through the integration of Failure Mode and Effect Analysis (FMEA) in the Quality Control Circle (QCC). The initial analysis identified a major problem in the form of damage to the wiper components that caused the product defect. The main causes include materials that are too hard, lack of spare stock, and the absence of standard wiper radius specifications. The solutions implemented include changes in the technical specifications of wipers, the manufacture of stock control systems, and the standardization of production processes. The results of the evaluation showed a 50% reduction in the frequency of damage, from a total of 17 problems to 8 problems, and an increase in production efficiency. The QCC-based approach has proven to be effective in improving the performance of the production process in a sustainable manner.